Ultra-Wideband (UWB) Radar for the Remote Measuring of Main Parameters of Patient's Vital Activity - Immoreev, I.J.; Samkov, S.V. (Радиофизика и радиоастрономия, 2002)
The capability of UWB radar usage in medicine the for remote measuring of patient’s heart activity and respiration is considered. The measuring method is described and practical results of the tests are cited. The possibility of the radar implementation in some other fields is shown. Рассматривается возможность использования широкополосного радара в медицине для дистанционного измерения сердечной и дыхательной деятельности пациентов. Описан метод измерений и приведены практические результаты исследований. Розглянуто можливість використання широкосмугового радара в медицині для дистанційного вимірювання серцевої та дихальної діяльності пацієнтів. Описано метод вимірювань та наведено практичні результати досліджень.